Asuhan Keperawatan pada An. A dengan Pneumonia di Ruang Anggrek Rumah Sakit Umum Kota Tangerang Selatan - Ulida, Rahma; Jansen, Susiana (Yayasan Penelitian dan Pengabdian Masyarakat Sisi Indonesia, 2024)
Background: Preschool children are a time when children's potential can develop optimally if they are paid attention to from an early age. The World Health Organization (WHO) states that Upper Respiratory Tract Infections (ARI) are still the biggest cause of death in children under 5 years old throughout the world, namely almost 20%, one of which is pneumonia. Pneumonia can cause airway obstruction, characterized by an increase in respiratory frequency. Blowing balloons is a breathing exercise with play therapy that aims to overcome increased respiratory frequency. Objective: to analyze nursing care by applying breathing exercises through balloon blowing play therapy for children who experience increased respiratory frequency. Method: research uses case studies in the form of case reviews to explore the problem of nursing care in An. A with Pneumonia in the Orchid Room at South Tangerang City General Hospital. Results: the application of breathing exercise through balloon blowing play therapy which was carried out once a day for 3 days, to overcome the increase in respiratory frequency had a good effect. The average decrease in respiratory frequency that occurs is 3-5 x/minute. Conclusion: The success of implementing breathing exercises through balloon blowing play therapy is also due to supporting factors such as collaboration in providing expectorants/mucolytics/bronchodilators, good eating patterns in accordance with adequate nutritional intake, advice on changing the semi-Fowler/Fowler position and teaching effective coughing techniques.